The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0093854819842907
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Future Offending in Child and Adolescent Firesetters Following a Fire Service Intervention Program

Abstract: Research has established links between youth firesetting and general antisocial behavior. The current study sought to better understand these links by identifying fire-specific and general risk factors for offending from a national sample of children and adolescent firesetters ( N = 1,790), from a New Zealand Fire Service intervention program, up to 10 years after intervention. Most (62%) had committed an offense post-intervention, primarily moderate or severe offending. Only 5% had committed an arson offense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…It therefore seems that fire safety education intervention as the sole treatment is effective for most (two-thirds) young people who engage in firesetting behavior, but not sufficient to eradicate this behavior for all participants. The rate of persistent firesetting is consistent with a recent meta-analysis investigating firesetter reoffending (Perks et al, 2019), but higher than the rare studies reporting evaluations of firesetter interventions specifically (e.g., Lambie et al, 2019;5% arson recidivism). These discrepancies in persistent firesetting figures are likely to be a result of the varied measurement of persistent firesetting used as an indication of program success (e.g., criminal convictions of fire offenses verses parent-report firesetting and/or matchplay).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It therefore seems that fire safety education intervention as the sole treatment is effective for most (two-thirds) young people who engage in firesetting behavior, but not sufficient to eradicate this behavior for all participants. The rate of persistent firesetting is consistent with a recent meta-analysis investigating firesetter reoffending (Perks et al, 2019), but higher than the rare studies reporting evaluations of firesetter interventions specifically (e.g., Lambie et al, 2019;5% arson recidivism). These discrepancies in persistent firesetting figures are likely to be a result of the varied measurement of persistent firesetting used as an indication of program success (e.g., criminal convictions of fire offenses verses parent-report firesetting and/or matchplay).…”
Section: Discussionsupporting
confidence: 85%
“…Fire service‐led intervention programs can often be a first‐point of professional contact for young people with problematic underlying psychosocial disturbances when firesetting behavior is identified (Henderson et al, 2010 ; Lambie et al, 2019 ). Although fire safety education delivered by fire services is viewed as appropriate for low‐risk firesetters, a review of interventions conducted by Baretto et al ( 2004 ) reported that evidence suggests fire safety education alone has limited effectiveness for eradicating firesetting behavior in young people marked by significant behavioral or emotional disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence base is expanding, with more sophisticated evaluations of firesetting treatment emerging. For example, Lambie et al (2019) followed a national sample (n = 1,790) of children who had been through the New Zealand Fire Awareness and Intervention Programme (FAIP). They found that, according to police records, 62% engaged in a further offense of any kind and 5% committed arson over the 10 years following the intervention.…”
Section: How Common Is General Reoffending?mentioning
confidence: 99%
“…Mental illness more broadly has been more consistently associated with fire-setting, particularly schizophrenia, mood disorders, personality disorders, and alcohol abuse (Nanayakkara et al, 2015;Sambrooks et al, 2021), but again the majority of people who commit arson do not have a diagnosed mental illness (Tyler & Gannon, 2012). Lastly, research has reported that fire interest and play are relatively normative developmental behaviours during childhood, and a substantial proportion of suspicious fires (50-63%) within Aotearoa New Zealand are attributed to young people (Fire and Emergency New Zealand, 2011;Lambie et al, 2019). However, due to the emphasis on diversion services in youth justice, relatively few young people are charged or convicted for arson.…”
Section: Researchmentioning
confidence: 99%
“…In comparison, there were 26,630 charges for sexual assault or related offences within this time period (2016-2020), 47.9% of which resulted in a conviction (Ministry of Justice, 2021a). Although youth are thought to be responsible for approximately half of all suspicious fires, the vast majority of charges and convictions are made against adults (Fire and Emergency New Zealand, 2011;Lambie et al, 2019;Ministry of Justice, 2021b). This is likely due to the focus on diversion services within Aotearoa New Zealand's youth justice system (Barretto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%